BIOLEACHING OF LATERITIC NICKEL ORE FROM POMALAA BY UTILIZING ASPERGILLUS NIGER FUNGAL CONSORTIUM - KUSUMA, HARDY
Bioleaching is one of the alternative methods for extracting nickel from lateritic ore which is still being developed. This method has several advantages, such as requiring low energy consumption and does not consume much leaching reagent due to self-capability of system to generate acid from microorganism metabolic procesess. In this final project research, bioleaching of lateritic nickel ore of limonite and saprolite types from a mine area in Pomalaa (South East Sulawesi) by using consortium of Aspergillus niger fungus has been studied. Aspergillus niger is a fungus that has been commonly used in the production of citric acid. The purpose of the research work is to study the influences of ore types, ore particle size distribution, solid percentage, sulphur addition, inocullum percentage, substrate volume percentage on nickel extraction percentage and selectivity of bioleaching to iron and magnesium. The life cycle of Aspergillus niger was also predicted by evaluating the effect of the medium for fungus growth addition (i.e. Potato Dextrose Broth) along with new fungus innoculum after 16 days of leaching on the percentage of nickel extraction. Series of lateritic nickel ore from Pomalaa bioleaching by using consortium of Aspergillus niger fungus was started with the adaptation of the Aspergillus niger fungus into the substrate of acid mine water to ensure that the fungus can survive in a very acidic condition. Shake flask bioleaching assays were carried out in rotating shaker for twenty seven (27) days, under shaking speed of 200 rpm at room temperature. The bioleaching assays were performed under the variations of ore types (i.e. saprolite and limonite), ore size distribution (-60+80 mesh, -100+200 mesh, and -200 mesh), solid percentage (2,5% w/v and 5% w/v), acid mine water volume percentage (5% v/v and 10% v/v) and the amount of sulphur addition (5% w/w and 10% w/w of the ore weight). As comparison, leaching tests ware also conducted by using commercial citric acid for twenty seven (27) days in the similar rotating shaker. Leach solution samples were taken nine times during the period of leaching process, every three or four days. Atomic Absorption Spectrophotometry (AAS) analysis was performed to measure the concentrations of dissolved nickel, iron, and magnesium in the solution samples. Based on the results of AAS analysis, nickel extraction percentages and selectivity of bioleaching at various conditions were determined. Fluorescence Diacetate Analysis (FDA) was also done to determine the enzymes activity that indicates the fungus activity during the bioleaching process. The investigation results showed that the bioleaching of nickel laterite ore by using Aspergillus niger fungal consortium is more effective for saprolite ore. The highest nickel extraction percentage of 43% derived from saprolite ore bioleachingexperiments on particle size distribution of -60 +80 mesh, solid percentage (pulp density) 2.5% w/w, fungal innoculum of 20% v/v, volume of organic substrates 10%, and the addition of 10% w / w sulfur after 19 days of leaching. Meanwhile, the limonite ore bioleaching process gives the highest percentage of nickel extraction 22% obtained in the experiment with the distribution of -60 +80 mesh particle size, solid percentage (pulp density) 5% w/v, the amount of fungal innoculum 20% v/v, volume of water mine acid 10% v/v, and the addition of 10% sulfur after 24 days. From the analysis of the FDA known that after two weeks, the activity of microorganisms decreased significantly, so it can be concluded that the Aspergillus niger’s life cycle is relatively short which is about two weeks. Potato Dextrose Broth and the addition of new fungus after 16 days, re-increase the percentage of nickel extraction which tends to fall after 2 weeks. Saprolitic ore bioleaching shows a very well selectivity value of magnesium, with the best selectivity value of 0.95 for the scale of 0-1, while the selectivity value of iron is 0.87. For limonite ore bioleaching, bioleaching selectivity against iron and magnesium respective saline at 0.92 and 0.79. For commercial citric acid leaching process, nickel extraction percentage obtained show better results than bioleaching process, with 92.7 percent extraction of nickel for saprolite ore, and 35.6 percent extraction of nickel for limonite which obtained at a concentration of 2M citric acid for 24 days leaching with the ore size distribution of -200 mesh. Same as bioleaching experiments’ results, chemical leaching experiments with commercial citric acid shows excellent selectivity against magnesium for saprolite ore.